Wellness Tourism Development Strategy for Poncokusumo Tourism Village, Malang Regency - Audrey Savatiara Krisner; Ida Ayu Rostini; Edvin Fairliantina; Lesfandra Lesfandra (Jurnal Info Sains : Informatika dan Sains, 2026)
The Indonesian tourism sector faces challenges in improving sustainability and competitiveness. One emerging approach is wellness tourism, which emphasizes the health and well-being of tourists. Poncokusumo Tourism Village in Malang Regency serves as an example, with the attraction of Pondok Ashitameru, which offers forest bathing, meditation, and trekking activities. This study aims to formulate a development strategy for Poncokusumo Tourism Village as a wellness tourism destination. The method used is descriptive qualitative through observation, interviews, questionnaires with 64 respondents, and a SWOT analysis to identify strengths, weaknesses, opportunities, and threats. The results show that Poncokusumo Tourism Village is positioned in quadrant I (Strength–Opportunity) or a rapid growth strategy. The formulated strategies include diversification of wellness tourism products, strengthening policies through partnerships, developing infrastructure and health services, increasing human resource capacity, innovation and multi-stakeholder collaboration, and digital promotion. This study recommends the preparation of sustainability-based planning documents, active support from local governments, and synergy between the government, the private sector, and the local community so that Poncokusumo Tourism Village can become a leading wellness tourism destination in East Java.